Nigerian Enterprise Sector and Policy Uncertainty - R, Ukwueze Ezebuilo; T, Asogwa Henry; C, Odo Augustine (Asian Journal of Economic Modelling, 2018)
This study evaluates the Nigerian enterprise sector and policy uncertainty using the World Bank enterprise survey data for Nigeria 2010. Using the multinomial logistic regression model and the multivariate analysis to specifically analyze the impact of policy uncertainty on the enterprise sector and the factors that have influenced the growth of the Nigerian enterprise sector, the findings show that tax rate, customs and trade regulations and macroeconomic environment have impacted on the medium and large enterprise sector positively. The findings also showed that in the small enterprise sector, labour regulation, licensing and permits, policy uncertainty and political instability have negative impact on the medium and large sector enterprise sector in Nigeria. Meanwhile, electricity, unskilled workforce, cost of finance, practice of competitors, power outages and cost of raw materials or intermediate goods all have positive influence the growth of the Nigeria enterprise sector. The study recommends that proper macroeconomic environment, strong institutions, good leaderships and infrastructures will both enhance public and private sector productivity for economic competitiveness.